2017
DOI: 10.1111/odi.12721
|View full text |Cite
|
Sign up to set email alerts
|

“Assessment of relationship between xerostomia and oral health‐related quality of life in patients with rheumatoid arthritis”

Abstract: Because there seem to be a high prevalence of xerostomia in patients with rheumatoid arthritis, screening in such population is highly recommended. Therefore, educational programs and/or workshops should be encouraged among healthcare providers to prevent worsening of oral health-related quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
(55 reference statements)
2
24
0
2
Order By: Relevance
“…One of these studies applied OHIP 14 questionnaire and found a mean value of 9.97, what is just slightly lower than in the current study (Yuen & Nelson, 2014). The largest body of studies is available for patients with RA, which also confirmed an impaired OHRQoL in this patient group (Blaizot et al., 2013; Chamani et al., 2017; de Azevedo Branco et al., 2019; Mühlberg et al., 2017; Nosratzehi, Nosratzehi, Nosratzehi, & Ghaleb, 2019; Schmalz et al., 2020; Tristiu et al., 2018). The OHIP G14 sum score in the current study lied between the scores of two previous German studies, which showed values of 5.4 and 7.7, respectively (Mühlberg et al., 2017; Schmalz et al., 2020).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…One of these studies applied OHIP 14 questionnaire and found a mean value of 9.97, what is just slightly lower than in the current study (Yuen & Nelson, 2014). The largest body of studies is available for patients with RA, which also confirmed an impaired OHRQoL in this patient group (Blaizot et al., 2013; Chamani et al., 2017; de Azevedo Branco et al., 2019; Mühlberg et al., 2017; Nosratzehi, Nosratzehi, Nosratzehi, & Ghaleb, 2019; Schmalz et al., 2020; Tristiu et al., 2018). The OHIP G14 sum score in the current study lied between the scores of two previous German studies, which showed values of 5.4 and 7.7, respectively (Mühlberg et al., 2017; Schmalz et al., 2020).…”
Section: Discussionmentioning
confidence: 74%
“…Generally, oral health parameters like tooth loss and periodontitis severity affect the OHRQoL (Buset et al, 2016;Gerritsen, Allen, Witter, Bronkhorst, & Creugers, 2010). Some previous studies are available, confirming the association between tooth loss or denture wearing and OHRQoL of patients with rheumatic diseases, respectively (Blaizot et al, 2013;Chamani et al, 2017;Corrêa et al, 2018;Schmalz et al, 2020). In contrast, several other examinations showed no associations between oral status and OHRQoL of patients suffering from rheumatic disease (Mühlberg et al, 2017;Schmalz et al, 2018;Tristiu et al, 2018).…”
Section: Comparison With International Literaturementioning
confidence: 93%
“…This result underlines the complexity of the patient group and OHRQoL. In this respect, xerostomia may also be a major factor affecting OHRQoL in RA patients that may also be of relevance [17], which was not considered in the current examination. Nevertheless, the current study provides new insights regarding the OHRQoL of RA patients with potential clinical relevance.…”
Section: Discussionmentioning
confidence: 88%
“…Furthermore, patients with RA were found to show an increased number of missing teeth [14][15][16]. Moreover, disease-or medication-related complaints such as xerostomia can reduce OHRQoL in patients suffering from RA [17]. In contrast, a recent study showed the impaired OHRQoL to be independent of the oral health condition [9].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the drugs can be associated with adverse events in the oral cavity, such as changes in mucous membranes and other symptoms different from patient to patient 23. About half of the patients with RA (51.5%) complain xerostomia and, consequently, difficulties in swallowing and phonation, sensation of burning mouth, increased thirst, loss of taste, unpleasant taste and odor and dental sensitivity 24 .…”
Section: Introductionmentioning
confidence: 99%